PECULIARITIES OF MONETARY SUPPORT OF THE ARMED FORCES OF UKRAINE UNDER MARTIAL LAW - Gorodianska, L. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2022)
During the period of war and the introduction of the legal regime of martial law, the amount of expenses for the financial support of the functioning of the defense and security sector of Ukraine increased significantly compared to those planned in the State Budget for 2022. The analysis was made on the basis of generalizing the losses of the state budget and the lost financial opportunities of Ukraine in the conditions of Russia’s armed aggression. The state budget of Ukraine is the basis for the financial support of the defense capability, maintaining the financial stability and security of the state. During the war, the government took prompt action to transform the financial system of the state. The features of adaptation under martial law of the military state of the system of monetary support for military personnel and employees of the Armed Forces of Ukraine as a component of the financial system of the state are revealed. Analysis of the changes the current regulatory framework, which were implemented by the Government of Ukraine in a state of martial law, made it possible to peculiarities the features that have occurred in the monetary support of military personnel and employees of the Armed Forces of Ukraine. For researching the peculiarites of the legal regulation of the system of monetary support for military personnel and employees of the Armed Forces of Ukraine in the conditions of martial law, a systematic approach was applied. An analysis was made of the legal framework governing the financial and legal aspects of the functioning of the system monetary support for military personnel, on the basis of which the concept of "the system of monetary support" for military personnel was clarified. The structure has been formed and the new values of monetary support for military personnel in war conditions have been specified. It was clarified that the personnel of the Armed Forces of Ukraine consists of military personnel and employees of the Armed Forces of Ukraine who are citizens of Ukraine. Generalize of reguliarities of labor relations and guaranteeing the preservation of the place of work (position) and the average earnings of employees, including employees of the Armed Forces of Ukraine in the context of the introduction of the legal regime of martial law, are summarized.